Classification of Sequences Generated by Compression and Encryption Algorithms - Kozachok, Alexander; Andreevich, Spirin Andrey (Journal of Science and Technology on Information security, 2020)
Abstract—An approach to the formation of the voice signal (VS) informative features of the Vietnamese language on the basis of stationary autoregressive model coefficients is described. An original algorithm of VS segmentation based on interval estimation of speech sample numerical characteristics was developed to form local stationarity areas of the voice signal. The peculiarity is the use of high order autoregressive coefficients, the set of which is determined on the basis of discriminant analysis. Tóm tắt— Bài báo mô tả một cách tiếp cận để tạo ra các đặc trưng thông tin tín hiệu thoại (VS-voice signal) của tiếng Việt trên cơ sở các hệ số của mô hình tự hồi quy dừng. Một thuật toán độc đáo để phân đoạn tín hiệu thoại dựa trên ước tính khoảng của các đặc trưng số mẫu tiếng nói đã được phát triển để tạo ra các vùng tĩnh cục bộ của tín hiệu thoại. Điểm đặc biệt là việc sử dụng các hệ số tự hồi quy bậc cao, tập hợp của chúng được xác định trên cơ sở phân tích biệt thức.